MYCN is retained in single copy at chromosome 2 band p23-24 during amplification in human neuroblastoma cells. - Corvi, R (1994)
Amplification of the human N-myc protooncogene, MYCN, is frequently seen either in extrachromosomal double minutes or in homogeneously staining regions of aggressively growing neuroblastomas. MYCN maps to chromosome 2 band p23-24, but homogeneously staining regions have never been observed at this band, suggesting transposition of MYCN during amplification. We have employed fluorescence in situ hybridization to determine the status of MYCN at 2p23-24 in five human neuroblastoma cell lines. All five lines carried, in addition to amplified MYCN in homogeneously staining regions or double minutes, single-copy MYCN at the normal position. In one line there was coamplification of MYCN together with DNA of the host chromosome 12, to which MYCN had been transposed. Our results suggest a model of amplification where MYCN is retained at its original location. They further sustain the view that either the initial events of MYCN amplification or the further evolution of amplified MYCN copies follow mechanisms different from those leading to amplification of drug-resistance genes.